KEBIJAKAN FORMULASI PENGATURAN PEMBUATAN PASPOR DITINJAU DARI PASAL 126 HURUF C UNDANG UNDANG KEIMIGRASIAN - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Immigration has a role as a gatekeeper of the state,as a regulator and supervisor of entry and exit of people in the territory of Indonesia. Therefore, everyone is required to have a passport. In the process of making a passport, if the information provided is incorrect, the passport applicant will be subject to criminal sanctions. Based on the article, the formulation of the problem is: how is the passport process 126 Letter c of Law Number 6 of 2011 concerning Immigration to provide legal certainty? and how is the formulation policy for regulating the process of making the passport of the Republic of Indonesia in providing information that is not really from the perspective of the Ius Constituendum? The research method used is a normative research type, using a statute approach, and a comparative approach. Using primary, secondary and tertiary legal materials. The technique of collecting legal materials is by literature study, the technique of analyzing legal materials is by using descriptive analysis. The results of this study indicate that the passport making process is carried out through the Online Passport Service application. If there is an indication that the information submitted is not true (false or false information) then the judge can make a grammatical interpretation so that there is legal certainty. The formulation policy for regulating the process of making passports for the Republic of Indonesia in relation to providing incorrect information from the perspective of the Ius Constituendum, is the formulation of criminalization patterns in